Maize Yield and Planting Date Relationship: A Synthesis-Analysis for US High-Yielding Contest-Winner and Field Research Data - Long, Nguyen V.; Assefa, Yared; Schwalbert, Rai; Ciampitti, Ignacio A. (Frontiers in Plant Science, 2017)
For maize (Zea mays L.) crop, planting date and yield relationships from field-research data are documented in the scientific literature. Nonetheless, a review of high yielding contest-winners’ data and research studies on the effects of planting date and yield for maize is not yet available. Following this rationale, a synthesis-analysis was conducted from farmer annual maize contest-winners’ data (n = 16,198 data points; 2011-2016 period) cordially provided by the National Corn Growers Association (NCCA) and a literature dataset collected from peer-reviewed scientific studies published during the last three decades. The main objectives of this study were to: (i) identify spatial yield variability under high yield environment; (ii) understand the impacts of planting date on yield variability; (iii) explore the effect of management practices on maize yield and planting date relationship, and (iv) utilize the maize planting date dataset collected via farmer contest-winners to benchmark against the compendium of scientific literature available for yield and planting date relationship for the main US maize producing regions. Major findings of this study are: (i) a significant correlation between planting date and latitude was established, (ii) maize yield was maximized when the planting window was 89-106 day of the year (DOY) for the 30-35 oN, 107-118 DOY for the 35-40 oN, <119 DOY for 40-45oN and <129 DOY for 45-50 oN, and iii) both the yield contest and literature datasets portrayed that planting date becomes a more relevant factor when planting late, presenting a small planting window in high- compared to low-latitudes.